Mycorrhizas alter sucrose and proline metabolism in trifoliate orange exposed to drought stress - Wu, Hui-Hui; Zou, Ying-Ning; Rahman, Mohammed Mahabubur; Ni, Qiu-Dan; Wu, Qiang-Sheng (Scientific reports, 2017)
Arbuscular mycorrhizal fungi (AMF) can enhance drought tolerance in plants, whereas little is known regarding AMF contribution to sucrose and proline metabolisms under drought stress (DS). In this study, Funneliformis mosseae and Paraglomus occultum were inoculated into trifoliate orange (Poncirus trifoliata) under well watered and DS. Although the 71-days DS notably (P < 0.05) inhibited mycorrhizal colonization, AMF seedlings showed significantly (P < 0.05) higher plant growth performance and leaf relative water content, regardless of soil water status. AMF inoculation significantly (P < 0.05) increased leaf sucrose, glucose and fructose concentration under DS, accompanied with a significant increase of leaf sucrose phosphate synthase, neutral invertase, and net activity of sucrose-metabolized enzymes and a decrease in leaf acid invertase and sucrose synthase activity. AMF inoculation produced no change in leaf ornithine-δ-aminotransferase activity, but significantly (P < 0.05) increased leaf proline dehydrogenase activity and significantly (P < 0.05) decreased leaf both Δ1-pyrroline-5-carboxylate reductase and Δ1-pyrroline-5-carboxylate synthetase activity, resulting in lower proline accumulation in AMF plants under DS. Our results therefore suggest that AMF strongly altered leaf sucrose and proline metabolism through regulating sucrose- and proline-metabolized enzyme activities, which is important for osmotic adjustment of the host plant.
Keywords: Proline; Colony Count, Microbial; Droughts; Poncirus; Glomeromycota; Seedlings; Mycorrhizae; Sucrose; listy rostlin; metabolismus sacharidů; prolin; semenáček; Carbohydrate Metabolism; Plant Leaves; Stress, Physiological; období sucha; mykorhiza; fyziologický stres; voda; sacharosa; Water; počet mikrobiálních kolonií